Immunochemical analysis of the interaction of p53 with MDM2;--fine mapping of the MDM2 binding site on p53 using synthetic peptides - Picksley, Steven M; Vojtěšek, Bořivoj; Sparks, Alison; Lane, David P (Oncogene, 1994)
The function of p53 is modulated by binding to a number of cellular and viral proteins, such as MDM2 and SV40 large T antigen. An initial immunochemical characterization of the p53-MDM2 complex in a rat fibroblast cell line (Clone 6) suggested that the anti-p53 monoclonal antibody Bp53-19 failed to immunoprecipitate the complex, and only recognized a fraction of the available p53 protein. Following the recent identification of the Bp53-19 epitope at the N-terminal end of p53, in the vicinity of where MDM2 protein was known to bind, we investigated the possibility that Bp53-19 might identify a region of p53 that interacts with MDM2 protein. MDM2 was found to bind with great specificity to short synthetic peptides derived from the N-terminus of p53. Several p53 synthetic peptides libraries, and an alanine substitution series at the optimal binding site, were used to establish the MDM2 binding site, in fine detail, to the sequence TFSGLW (aa 18-23) in mouse and TFSDLW in man (aa 18-23). The key residues required for MDM2 binding are almost identical to those required for the monoclonal antibody Bp53-19 to bind and this region of p53 is recognised by many other anti-p53 antibodies.
Keywords: Immunochemistry; nádorové proteiny; Male; vazebná místa; protoonkogenní proteiny c-mdm2; Proto-Oncogene Proteins; molekulární sekvence - údaje; Amino Acid Sequence; jaderné proteiny; mužské pohlaví; nádorový supresorový protein p53; imunochemie; Proto-Oncogene Proteins c-mdm2; peptidové fragmenty; kultivované buňky; Binding Sites; Animals; zvířata; sekvence aminokyselin; myši; Neoplasm Proteins; Cells, Cultured; Molecular Sequence Data; Mice; Peptide Fragments; Nuclear Proteins; Tumor Suppressor Protein p53; protoonkogenní proteiny